(3GdEdeGe HGdQhV hSjQI GHf gTGe GdedbH HLdGA GdCacGQ HSjQI GdeNJGQs - (3CHi GdaJM eMeO Hf EHQGgje Hf eMeO Hf ebHd GdHdjSi GdebOSi GdOeTbj GdTGaYjs; (3YHO GdQMef Hf YHO Gddg Hf CMeO GdNKYeqj GdSgjdqj,J (B581 (3g` s
(3ChdgG (B:s
(3jbhd GdabjQ Edi Gddg YR hLd ai Schfg hMQcJg NGOe GdSfI GdTQjaI HOeTb GdeMQhSI s
(3BNQgG (B:s
(3hYefG HQCaJc GPG NdJ efG GdOhR GddMhO hGfTQ YdjfG LfGM QVhGfc Je QGdLRA GdChd ef cJGH s
(3hHChdg agQS HGdCUhd GdeSJfO efgG gPG GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs